Paraoxonase-1: Characteristics and Role in Atherosclerosis and Carotid Artery Disease - Lioudaki, S.; Verikokos, C.; Kouraklis, G.; Ioannou, C.; Chatziioannou, E.; Perrea, D.; Klonaris, C. (Current Vascular Pharmacology, 2019)
Paraoxonase-1 (PON-1) is a calcium-dependent enzyme that is synthesized in the liver and then secreted in blood where it is bound to high density lipoprotein (HDL). PON-1 is a hydrolase with a wide range of substrates, including lipid peroxides. It is considered responsible for many of the antiatherogenic properties of HDL. PON-1 prevents low density lipoprotein (LDL) oxidation, a process that is considered to contribute to the initiation and development of atherosclerosis. PON-1 activity and levels are influenced by gene polymorphisms; of the 2 common variants, one is in position 192 (Q192R) and one in position 55 (M55L). Also, many drugs affect PON-1 activity. The role of PON-1 in carotid atherosclerosis is inconsistent. Some studies show an association of PON-1 polymorphisms with carotid plaque formation, whereas others do not. The aim of this review is to summarize the characteristics of PON-1, its interactions with drugs and its role in atherosclerosis and especially its relationship with carotid artery disease.
Keywords: Paraoxonase